Pyelolithotomy in a Patient with Complete Coraliform Calcification Induced by a Double-J Ureteral Stent - Miguel Bonfitto; Analaura de Oliveira Cury; Victoria Caroline Pagelkopf; Vinicius Ramos Bezerra de Morais; Carlos Abib Cury (Case Reports in Urology)
The placement of a double-J ureteral stent enables the treatment of upper urinary tract obstruction. Despite advances, forgetting the stent favors the occurrence of calcification, leading to increased morbidity rates, lawsuits, and a financial burden on the healthcare system. This paper describes a successful pyelolithotomy for the removal of a calcified double-J ureteral stent.